Depletion of Non-Renewable Resources and Endogenous Technical Change - Jürgen Antony (Universität Augsburg, Institut für Volkswirtschaftslehre, 2007)
Non-renewable resources are an obstacle for positive long run growth if they are essential for production, households solve an intertemporal Ramsey problem and population is growing. Modern growth models predict that growth is positively related to growth in production factors. Hence, there are opposing forces at work if labor as one factor is growing and the use of the non-renewable resource as another factor is shrinking. The paper develops a semi-endogenous growth model with one labor and one resource using sector and derives conditions for stable positive long run growth in per capita production and consumption.
urn:nbn:de:bvb:384-opus4-711459
Keywords: O33; O31; Q32; 330; Non-renewable resources; semi-endogenous growth